2015
DOI: 10.1097/md.0000000000000675
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Hepatitis E Virus Infection in Patients With Inflammatory Arthritides Treated With Immunosuppressants

Abstract: The clinical presentation and outcome of hepatitis E virus (HEV) infection in inflammatory rheumatic diseases are unknown. We aimed to investigate the severity of acute HEV infection and the risk of chronic viral replication in patients with inflammatory arthritides treated with immunosuppressive drugs.All rheumatology and internal medicine practitioners belonging to the Club Rhumatismes et Inflammation in France were sent newsletters asking for reports of HEV infection and inflammatory arthritides. Baseline c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 20 publications
0
46
1
3
Order By: Relevance
“…However, Senosiain et al [281] found a lower prevalence among patients with inflammatory bowel disease than for the general population. Similarly, Bauer et al [282] studied the HEV infection in patients with inflammatory arthritides under immunosuppressive therapy, but no chronic infection was observed.…”
Section: Routes Of Transmission and Risk Groupsmentioning
confidence: 99%
“…However, Senosiain et al [281] found a lower prevalence among patients with inflammatory bowel disease than for the general population. Similarly, Bauer et al [282] studied the HEV infection in patients with inflammatory arthritides under immunosuppressive therapy, but no chronic infection was observed.…”
Section: Routes Of Transmission and Risk Groupsmentioning
confidence: 99%
“…This patient had a benign self-limiting course of HEV infection [18]. In a French study, 23 cases of HEV infection in patients with rheumatoid arthritis, axial spondyloarthritis, psoriatic arthritis, and other types of arthritides under immunosuppressive therapy regimens were studied [19]. The treatment included discontinuation of immunosuppressants in 20 patients and ribavirin treatment in 5 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic HEV infection is almost exclusively reported in immunosuppressed patients. This group includes patients with solid organ transplantation (SOT), patients on chemotherapy for haematologic malignancies, patients infected with HIV and patients with rheumatologic conditions receiving immunomodulatory drugs . Chronic HEV in the SOT population is almost exclusively attributable to genotype 3 infection.…”
Section: Chronic Hev Infectionmentioning
confidence: 99%
“…This group includes patients with solid organ transplantation (SOT), 5 patients on chemotherapy for haematologic malignancies, 7 patients infected with HIV 8 and patients with rheumatologic conditions receiving immunomodulatory drugs. 9 Chronic HEV in the SOT population is almost exclusively attributable to genotype 3 infection. Indeed, chronic infection is not documented with HEV-1 and HEV-2.…”
Section: Chroni C He V Infec Ti Onmentioning
confidence: 99%
See 1 more Smart Citation